2021
DOI: 10.1002/jcp.30616
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction in meniscus fibrochondrocytes: What about caveolae?

Abstract: Meniscus fibrochondrocytes (MFCs) are an important cell population responsible for regulating the biomechanical properties of the knee meniscus. Despite their significance, not much is known about them, including how they sense and respond to mechanical stimuli. Due to the mechanical nature of the knee joint, it is therefore paramount to our understanding of the meniscus that its mechanotransductive mechanism be elucidated. In this review, we will summarize the current knowledge on mechanotransduction in MFCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, the mechanotransduction function of FOSB in MFCs ( Szojka et al, 2021a ) was reported by Szojka et al, and its function in the IL-17 signalling pathway was well demonstrated ( Benderdour et al, 2002 ). Finally, Vyhlidal et al recognized the potential of caveolae molecules such as CAV1/2 in the mechanotransductive mechanism of the meniscus, but this needs to be further verified in future studies ( Vyhlidal and Adesida, 2021 ). The transcriptome changes are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the mechanotransduction function of FOSB in MFCs ( Szojka et al, 2021a ) was reported by Szojka et al, and its function in the IL-17 signalling pathway was well demonstrated ( Benderdour et al, 2002 ). Finally, Vyhlidal et al recognized the potential of caveolae molecules such as CAV1/2 in the mechanotransductive mechanism of the meniscus, but this needs to be further verified in future studies ( Vyhlidal and Adesida, 2021 ). The transcriptome changes are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…This type of collagen fibers was also the main component in the outer region of the native meniscus [ 33 ]. It can assist meniscus to resist against circumferential tension and extrusion during suffering load [ 34 ]. The lack of collagen I may cause the function loss in resisting tensile load in the outer and intermedia region of meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the structural and mechanical cues that guide communication between a cell and its surrounding extracellular matrix (ECM) to promote regeneration is critical 6 . Further, a model that mimics the native mechanical properties of the knee meniscus is required to understand this mechanotransducive signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the structural and mechanical cues that guide communication between a cell and its surrounding extracellular matrix (ECM) to promote regeneration is critical. 6 Further, a model that mimics the native mechanical properties of the knee meniscus is required to understand this mechanotransducive signaling. The native equilibrium compressive modulus from human cadaveric meniscus tissue ranges from 50 to 1048 kPa, differing significantly across regions of the tissue.…”
Section: Introductionmentioning
confidence: 99%